Theories explaining the formation of the intellectual elite: A sociological reading - الله, ئاسۆ إبراهيم عبد; أبوبكرمحمد, پەروين (Sulaimani Journal for Humanities, 2019)
The chosen elite is one of the most important needs of any society because of its role and position in changing different parts of human society. The concept of Elite and Intelligentsia (the intellectual elite of a society) are different according to any society and culture's specific characteristics, it is a social and cultural norm that came from reality of the society. The atmosphere of civilization and history have a great role in creating features and characteristic of intelligentsia, the most favored and great kinds of group and can have a main role in making societies. They are the real doer of running the government and changing the values and manners, in addition to having an influential part of any society. This research claims a numbers of elite group and intelligentsia's theories which talks about the intellectual and cultural heritage of elite, with elite and intelligentsia's features, showing the effects and its role in social environment in creating intelligentsia and the influence of the elite in the society according their role and position in human society.